Family Status and Changing Workplace of Songkhla Commercial Sex Workers - Uahgowitchai, Powana; Uahgowitchai, Charn; Disornpong, Sutas; Chansorn, Sawang (Journal of Health Science of Thailand, 1994)
The STD and AIDS Regional Centre 12 has studied the social status and changing work-place of 450 Songkhla commercial sex-workers in August w November 1992. The results of this study were as follows: 1. Most of the female commercial sex workers came from the north (54.44%), norm-east (20.00%). Their mean income was 4238.33 baht/month. They had to take care of their parents (68.00%), send their children to study (10.00%) and build their houses (4.89%). 2. The sex-workers had changed their work-pl ace at least once (41. l l 70), including movement in the same province (32.42%)a movement across the province (67.57%). Songkran holiday was the most common period for them to go back home (58.07%). 3. The sex-workers were more from the North than other from regions (P<0.05). 4. The income per month and the responsibility in taking care of their parents were not statistically signiﬁcance with the thought to change their work-place, (P>0.05). As the result of this study, a good and effective follow-up system of these. female sex-workers should be established in order to be more effective in the prevention and control of STD and AIDS.